Structure and Biogenesis of Roussoellatide, a Dichlorinated Polyketide from the Marine-Derived Fungus Roussoella sp DLM33 - Ferreira, Everton L. F.; Williams, David E.; Ioca, Laura P.; Morais-Urano, Raquel P.; Santos, Mario F. C.; Patrick, Brian O.; Elias, Luciana M.; Lira, Simone P.; Ferreira, Antonio G.; Passarini, Michel R. Z.; Sette, Lara D. [UNESP]; Andersen, Raymond J.; et al. (Amer Chemical Soc, 2015)
The structure of the fungal metabolite roussoellatide (1) has been established by spectroscopic and X-ray diffraction analyses. Results from feeding experiments with [1-C-13]acetate, [2-C-13]acetate, and [1,2-C-13]acetate were consistent with a biosynthetic pathway to the unprecedented skeleton of 1 involving Favorskii rearrangements in separate pentaketides, subsequently joined via an intermolecular Diels-Alder reaction.